2013
DOI: 10.3899/jrheum.121377
|View full text |Cite
|
Sign up to set email alerts
|

Ms Hassanzadeh, et al reply

Abstract: Silverman featuring research articles on clinical subjects from scientists working is a monthly international serial edited by Earl D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Furthermore, marine bacteria can also degrade natural organic matter such as cellulose (by Cytophaga, Sporocytophaga), protein (by Pseudomonas), chitin (by Bacillus and Vibrio then pectin (by Clostridium pectinovorum) (Ghosh et al, 2011;Liang et al, 2021). The findings by Gómez-Consarnau et al (2019) and Hassanzadeh et al (2021) revealed marine bacteria possess rhodopsins that capture solar energy by an energy transducing mechanism reported to contribute rise in sea temperatures. Generally, the marine microbial community has a complex ecosystem, which is yet to be discovered, and new diversities impacts in oceans have not totally been explored.…”
Section: Diversity Of Marine Bacteriamentioning
confidence: 99%
“…Furthermore, marine bacteria can also degrade natural organic matter such as cellulose (by Cytophaga, Sporocytophaga), protein (by Pseudomonas), chitin (by Bacillus and Vibrio then pectin (by Clostridium pectinovorum) (Ghosh et al, 2011;Liang et al, 2021). The findings by Gómez-Consarnau et al (2019) and Hassanzadeh et al (2021) revealed marine bacteria possess rhodopsins that capture solar energy by an energy transducing mechanism reported to contribute rise in sea temperatures. Generally, the marine microbial community has a complex ecosystem, which is yet to be discovered, and new diversities impacts in oceans have not totally been explored.…”
Section: Diversity Of Marine Bacteriamentioning
confidence: 99%